2021
DOI: 10.1037/amp0000754
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences among youth from high-achieving schools: Appraising vulnerability processes toward fostering resilience.

Abstract: Among youth from high-achieving schools, adverse childhood experiences (ACEs) were examined in relation to (a) internalizing and externalizing symptoms in adolescence (n ϭ 527), and (b) symptoms plus psychiatric diagnoses-based on multiple annual interviews-in adulthood (n ϭ 316). Also examined were associations for a "Proxy ACEs" (P-ACEs) measure, containing items similar to those on standard ACEs measures without reference to abuse or neglect. Rates of ACEs were comparable with those in other studies; most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…More recent evidence, based on multiple high-achieving schools assessed between 2015 and 2019, reflects convergent findings (Luthar, 2019). The latter report presents new data on nine cohorts, including independent boarding, independent day, and public high schools, with a total sample of over 7,500 students.…”
Section: Evidence Of At-risk Statusmentioning
confidence: 95%
See 1 more Smart Citation
“…More recent evidence, based on multiple high-achieving schools assessed between 2015 and 2019, reflects convergent findings (Luthar, 2019). The latter report presents new data on nine cohorts, including independent boarding, independent day, and public high schools, with a total sample of over 7,500 students.…”
Section: Evidence Of At-risk Statusmentioning
confidence: 95%
“…Findings showed that across all nine schools and among both male and female students, rates of clinically significant anxious and depressed symptoms in particular were elevated, with a median value that was 6–7 times those in national norms. Rates of serious withdrawn–depressed and somatic symptoms were also high, with median values 3.5–5 times rates in nationally representative samples (Luthar, 2019).…”
Section: Evidence Of At-risk Statusmentioning
confidence: 99%
“…Consequences commonly include post-traumatic stress disorder (PTSD) [ 25 ], obesity and eating disorders [ 26 28 ], alcohol and drug problems [ 29 33 ], poor school achievement [ 34 ], depression [ 35 , 36 ], dissociation [ 37 ], social impairment [ 38 ], antisocial behaviour, anxiety [ 39 ], self-harm and suicide [ 40 , 41 ], and increased chance of revictimization [ 42 , 43 ]. In students from high-achieving schools, ACEs were associated with between two and five-fold increases in adult psychiatric diagnoses, depending on the extent of exposure to ACEs [ 44 ]. Reviews have highlighted the high rates of insecure disorganised and dissociative attachment styles in situations of severe and ongoing maltreatment [ 45 ].…”
Section: Epidemiology Of Childhood Maltreatmentmentioning
confidence: 99%
“…Veterans, particularly female veterans, are an important and understudied population and serve as the focus for study by Blosnich et al (2021) about the associations between ACEs and suicidal ideation. Luthar et al (2021) looks beyond more traditional target populations to examine a recently identified Group at risk for ACEs—youth from high-achieving schools.…”
Section: Critical Questionsmentioning
confidence: 99%